Pemilihan Batang Bawah dan Teknik Penyambungan Tanaman Jarak Pagar (Jatropha curcas) untuk Meningkatkan Potensi Produktivitas >10 ton/ha dan Tahan Terhadap Cekaman Kekeringan dalam Upaya Mendukung Pengembangan Bioenergi - . Hariyadi; Bambang Sapta Purwoko; . Djumali; Muhammad Cholid (Jurnal Ilmu Pertanian Indonesia, 2012)
Development of Jatropha in large scale in dryland requires plant material with high productivity and ability to adapt drought conditions. Attempt to maintain the stability of jatropha production in dry land can be done through grafting technology by combining the advantages of prospective shoot section which has high yield potential as a scion and rootstock candidates from plant material that is able to adapt to limited water availability. Three activities were carried out at the first year experiments including (1) selection method of drought stress that is fast, accurate and simple under laboratory condition, and (2) adaptability study of jatropha rootstock candidates associated with drought stress in glasshouse and in the field. The result showed that the method of drought stress that was fast, accurate and simple under laboratory condition was that using polyethylene glycol. Three jatropha rootstocks, namely IP-3M, Sulawesi 117, dan NTB 047, are tolerant to drought stress associated with drought stress both in glasshouse and in the field condition.